The agrarian economy of Oman (132-280/749-893) in Arabic sources - Ubaydli, Ahmad (Journal of Islamic Studies, 1993)
Conclusion (p. 48): the agrarian system which existed in Oman in the period under consideration (the first Ibāḍī state, 132-280/749-893), together with fishing and pearling and maritime trade, enabled the country to establish a base for economic self-reliance. This was manifested in a tendency to resist central authority. The Aflāj irrigation system in its Omani context made it possible for its users to be more independent and to have more influence over the local authorities. Ibāḍism seems to have reflected these two tendencies well enough for the Omanis to adopt it. Both classical Arabic and Omani sources reflect this situation and, taken together, provide a detailed description which illuminates various aspects of the agrarian economy that existed in Oman during this period.
Keywords: Agriculture – Oman

Democracy in the Islamic world: the agrarian economy as a base for early democratic tendencies in Oman - Ubaydli, Ahmad (Democracy in the Middle East : proceedings of the annual conference of the British Society for Middle Eastern Studies, 8-10 July 1992, University of St Andrews, Scotland., 1992)
Abstract at the beginning of the article: this paper intends to shed light on the agrarian economy in Oman and how it formed a base for democratic tendencies there 132-280/749-893, when the first independent state was established. The Falaj (pl. Aflāj) is an irrigation system where water is carried from source to the user area. Depending on such a system, agriculture in Oman thrived in comparison to the surrounding areas. The way the irrigation system is administered and the relatively ample agricultural products, together with other factors, established a real base for democratic tendencies. Ibāḍism was to a great extent a reflection of such a situation. Chapters on (the administration of) the Aflāj irrigation system, agricultural products, and Ibāḍism.
Keywords: Agriculture – Oman